Male Domination VS Early Feminism in The Scarlet Letter by Nathanial Hawthorne. - Mohammed Waleed Asaad, Asst. Lect. (Wasit Journal for Human Sciences, 2025)
This research focuses on the novel The Scarlet Letter by Nathaniel Hawthorne, which was first published in (1850) and is considered one of his most famous and influential works. The novel tells the story of a married woman who is tried for the crime of adultery after becoming pregnant by an unknown man during her husband’s absence, in a strictly religious Christian society in 17th-century Boston. The narrative delves into this woman’s (Hester’s) suffering following her scandal, and how she copes with her circumstances, after being forced to wear a scarlet letter (A) as a mark of shame and to be exiled.This study aims to shed light on the struggle and resistance of the charac+ter Hester—as well as her daughter Pearl—as a representation of feminism in the face of the dominance and control of the male characters in the novel, who serve as symbols of patriarchal authority. The novel is seen as one of the earliest seeds of successful feminism and rebellion against male or paternal oppression. The research will explore various aspects of the conflict between feminism and patriarchy on psychological, metaphorical, and physical levels.